Elucidating the microbiome of the sustainable peat replacers composts and nature management residues - Pot, Steffi; Tender, Caroline De; Ommeslag, Sarah; Delcour, Ilse; Ceusters, Johan; Vandecasteele, Bart; Debode, Jane; Vancampenhout, Karen (Frontiers in Microbiology, 2022)
Sustainable peat alternatives, such as composts and management residues, are considered to have beneficial microbiological characteristics compared to peat-based substrates. Studies comparing microbiological characteristics of these three types of biomass are, however, lacking. In this study weThis study examined examined if and how microbiological characteristics of subtypes of composts and management residues differ from peat-based substrates, and we determined how feedstock and (bio)chemical characteristics drive these characteristics. In addition, we evaluated microbiome characteristics were evaluated that may contribute to plant growth and health. These characteristics include: genera associated with known beneficial or harmful microorganisms, microbial and functional diversity/activity, microbial biomass, fungal to bacterial ratio and inoculation efficiency with the biocontrol fungus Trichoderma harzianum. Bacterial and fungal communities were studied using 16S rRNA and ITS2 gene metabarcoding, community-level physiological profiling (Biolog EcoPplates) and PLFA analysis. Inoculation with T. harzianum was assessed using qPCR. Samples of feedstock-based subtypes of composts and peat-based substrates showed similar microbial community compositions, while subtypes based on management residues were more difficult variable in their microbial community composition. For management residues, a classification based on pH and hemicellulose content may be relevant for bacterial and fungal communities, respectively. Green composts, vegetable, fruit and garden composts and woody composts show the most potential to enhance plant growth or to suppress pathogens for non-acidophilic plants, while grass clippings, chopped heath and woody fractions of compost show the most potential for blends for calcifuge plants. Fungal biomass was a suitable predictor for inoculation efficiency of composts and management residues.